2016
DOI: 10.1007/s12010-016-2107-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nanoparticles Against the Formation of Biofilm by Pseudomonas aeruginosa an In silico Approach

Abstract: Studies were undertaken to examine the mechanism of mediation of silver nanoparticles in inhibiting biofilm formation by Pseudomonas aeruginosa through LuxI/LuxR system of signal transduction. This study includes the basic signaling transduction mechanism LasR, QscR, RhlR, and Vfr signaling model systems. The arbitrary homology models built with the I-TASSER server were evaluated and validated with the Qmean web server. Based on the Z-score and the relative square mean distance (RMSD) values, the structures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
4
15
1
Order By: Relevance
“…Docking of known QSI such as furanone C30 (de Nys et al 2006) with LasR was also performed and showed similar interactions as those with the natural ligand, 3-oxo-C 12 -HSL ( Figure 8b). Docking studies of AgNP (Figure 8c) show electrostatic interaction with the amino acid Asp73 in a LasR active site which is same as in previously reported data (Vyshnava et al 2016). Eugenol displayed hydrogen bond interactions with the hydroxyl group of Tyr56 and Tyr93, hydrophobic interactions with Trp60, Tyr64, Trp88 and Ala127 and electrostatic interaction with Asp73 in the LasR active site, with the docking score 3,290 (Figure 8d).…”
Section: Lasrsupporting
confidence: 85%
See 1 more Smart Citation
“…Docking of known QSI such as furanone C30 (de Nys et al 2006) with LasR was also performed and showed similar interactions as those with the natural ligand, 3-oxo-C 12 -HSL ( Figure 8b). Docking studies of AgNP (Figure 8c) show electrostatic interaction with the amino acid Asp73 in a LasR active site which is same as in previously reported data (Vyshnava et al 2016). Eugenol displayed hydrogen bond interactions with the hydroxyl group of Tyr56 and Tyr93, hydrophobic interactions with Trp60, Tyr64, Trp88 and Ala127 and electrostatic interaction with Asp73 in the LasR active site, with the docking score 3,290 (Figure 8d).…”
Section: Lasrsupporting
confidence: 85%
“…In addition, these nanoparticles exhibited considerable anti-biofilm activity against P. aeruginosa, signifying their role in decreasing bacterial resistance towards traditional antibiotics. Although there have been previous studies on the in silico analysis of eugenol and silver nanoparticles using P. aeruginosa QS regulator proteins (Rathinam et al 2017;Vyshnava et al 2016), to the best of the authors' knowledge, this is the first report which shows a stable interaction of eugenol-conjugated silver nanoparticle against P. aeruginosa with LasI and LasR/MvfR quorum sensing regulators.…”
Section: Discussionmentioning
confidence: 88%
“…Hence, proteins are one of the attractive targets for finding new antimicrobial therapies. To date, it has been shown that AuNPs and AgNPs, along with their respective ions, interact with several structural proteins, membrane proteins and several enzymes [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In an experimental and molecular docking study, Shah et al evidenced the diverse action of AgNPs on various proteins of Pseudomonas aeruginosa [ 32 ].…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
“…Their overall experimental results gave proof of QS inhibition and biofilm destruction [ 32 ]. In a similar study, with homology modeling, Vyshnava et al showed interactions of four proteins involved in the signal transduction system of P. aeruginosa (LasR, QscR, RhlR and Vfr) with AgNPs, which resulted in their binding and inhibition [ 33 ]. In this study, it is reported that several amino acids—leucine, aspartate, arginine, lysine, tyrosine, arginine, alanine and tryptophan—from active sites of the four proteins interact with AgNPs [ 33 ].…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
See 1 more Smart Citation